2022
DOI: 10.15587/1729-4061.2022.265234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substitution of wheat flour with modified potato starch on the quality of Chinese steamed bread

Abstract: The application of potato starch in flour products is very important for potato staple food. The gluten protein of wheat flour will be weakened after being mixed with potato starch, which could have inhibitory effect on quality properties of flour products. Therefore, it is, it is necessary to study the influence of substitution wheat flour with potato starch on the quality of Chinese steamed bread (CSB), which is an important staple food in North China. This study investigated the effect of potato starch modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…HMT modified potato starch was prepared as the method previously reported by Deng (Deng et al, 2022a). The moisture content of starch was adjusted to 23.56%, then the starch was sealed and equilibrated 24 h at room temperature for moisture balance.…”
Section: Preparation Of Modified Potato Starchmentioning
confidence: 99%
“…HMT modified potato starch was prepared as the method previously reported by Deng (Deng et al, 2022a). The moisture content of starch was adjusted to 23.56%, then the starch was sealed and equilibrated 24 h at room temperature for moisture balance.…”
Section: Preparation Of Modified Potato Starchmentioning
confidence: 99%
“…Deng et al. (2023) reported that when modified potato flour is added in excess, wheat flour loses its gluten protein content, and the dough network weakens, resulting in noodles with poor texture characteristics. On the other hand, an increase in hardness with the substitution of wheat flour with potato flour has been reported by Pu et al.…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al. (2023) mentioned that by interacting with potato and wheat flour and increasing water absorption in the potato–wheat system, starch particles would fill in the gluten network, reducing dough elasticity and hindering the formation of gluten networks, which results in a reduction in pores and an increase in noodles' hardness.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to noodles crafted entirely from 100% rice flour, noodles manufactured using a blend of flour and JS-HMT starch exhibit an extended cooking time ranging from 373 to 414 s, coupled with an elevation in dry matter water absorption rate (139.40-157.20%), dry matter loss (1.61-5.25%) and breakage rate during cooking (1.42-1.72%). The higher the JS-HMT content, the more pronounced the alterations in the cooking characteristics of noodles become (Deng et al, 2023).…”
Section: Cooking Properties Analysis Of Rice Noodlesmentioning
confidence: 99%
“…The incorporation of HMT starch weakens the network structure in noodles, potentially causing the dissolution of watersoluble substances. This, in turn, increases the dry matter loss rate of noodles and may even lead to noodle breakage (Deng et al, 2023).…”
Section: Cooking Properties Analysis Of Rice Noodlesmentioning
confidence: 99%